Socio-Environmental Factors in Children with Autism Spectrum Disorders in Bangladesh (Bangladesh Journal of Child Health, 2020)
Background: Autism is a complex disorder resulting from the combination of genetic and environmental factors. Though various genetic factors are involved in expression of autism, exogenous factor can modify and control gene expression.Objectives: To find out the socio-environmental factors which may contribute to early development and expressions of autism in children of Bangladesh.Materials &Methods: Autism cases (n=652) were diagnosed clinically and by applying ICD10 criterions in Child Development Centers (CDCs) of 15 tertiary medical college hospitals of Bangladesh. A retrospective analysis was done on collected data of detailed history and clinical notes of those children.Results: Among total 652 children with autism, 71.9% were from 2-5 years’ age group at diagnosis, with a male predominance (79%). Seventy-two percent were from middle to higher income family groups, 68% from urban areas and maximum children from nuclear families (77.5%). ‘Less interactive family’ was found in 67.50%. Play opportunity was absent in 60.60%. All the children watched TV and 85.6% watched TV for more than 2 hours/day.Conclusion: Children from urban area, higher income and nuclear family, lack of interactive play opportunity may play important role to develop autism in Bangladeshi children.Bangladesh J Child Health 2020; VOL 44 (2) :78-81